Effect of sintering temperature on density, hardness and tool wear for alumina-zirconia cutting tool - A. B., Hadzley; T., Norfauzi; U. A. A., Umar; A. A., Afuza; M. M., Faiz; M. F., Naim (Universiti Malaysia Pahang, 2019)
Combination of alumina (Al2O3) and zirconia (ZrO2) as cutting tool have been established themselves as a dominant in ceramic category for dry machining. The mechanical properties of Al2O3-ZrO2 cutting tool were critically dependent on its density and hardness, which affected by the powder preparation and sintering processes. This paper present the effect of sintering temperature on density, hardness and tool wear of Al2O3-ZrO2 cutting tool. Specific composition of 80-90 wt% Al2O3 and 10-20 wt% ZrO2 powders were mixed and ball milled for 12 hours. These powders then were compacted in the form of RNGN120600 designated cutting tool by using manual hydraulic press before undergone secondary compaction by Cold Isostatic Press. The compacted powders then were sintered from 1200oC to 1400oC at constant 9 hours soaking time. For each sintered cutting tool, evaluation has been made based on the density and hardness. By using AISI 1045 as a workpiece material, the wear performance of the selected cutting tools were evaluated within 200-350 m/min cutting speeds, 0.1 mm/rev feed rate and 0.5 mm depth of cut. The results shows that the sintering temperature at 1400oC and 9 hours soaking time produced maximum relative density and hardness for 90 wt% Al2O3 and 10 wt% ZrO2 at 94.17% and 63.4 HRC respectively. Cutting tool contained with 80 wt% Al2O3 and 20 wt% ZrO2 contributed maximum relative density of 97% and hardness of 70.07 HRC. Maximum tool life recorded was 156s at 200 m/min cutting speed. Wear mechanisms of fabricated cutting tool dominated by the notch and flank wear at the early stage of machining and formation built up edge at the end of machining process.